Professional identity formation within longitudinal integrated clerkships: A scoping review. Issue 8 (24th February 2021) - Brown, Megan E. L.; Whybrow, Paul; Kirwan, Gavin; Finn, Gabrielle M.
Abstract: Context: Although the uptake of Longitudinal Integrated Clerkships (LICs) is increasing worldwide, and there are documented benefits to participation, there is a lack of conceptual evidence regarding how LICs exert many of their benefits, including their influence on the recruitment and retention of practitioners to underserved areas or specialties. Whilst career choice and professional identity development have been previously connected within medicine, what is known about the ways in which LICs influence identity remains unclear. A scoping review was conducted to explore current knowledge and map directions for future research. Method: In 2020, the authors searched nine bibliographic databases for articles discussing identity within the context of LICs using a systematic search strategy. Two reviewers independently screened all articles against eligibility criteria and charted the data. Eligible articles were analysed by quantitative and qualitative thematic analysis. Results: 849 articles were identified following an extensive search. 131 articles were selected for full‐text review, with 27 eligible for inclusion. Over half of all articles originated from the United States or Canada, and research most frequently explored identity development from sociocultural orientations. Qualitatively, four themes were identified: (a) The importance of contextual continuities; (b) Symbiotic relationship of responsibility and identity development; (c) Becoming a competent carer; and (d) Influence of LICs on career identity. Conclusions: This scoping review adds weight to the supposition that participation in LICs facilitates identity development, namely through contextual continuities and the responsibility students assume as they become co‐providers of patient care. There are suggestions that LICs encourage the development of an 'ethic of caring'. As little research compares comprehensive LICs with other clerkship models, it remains difficult to say to what degree identity formation is facilitated above and beyond other models. Future comparative research, and research exploring identity formation from diverse theoretical perspectives would add depth. Abstract : The authors explore what is known about identity development within Longitudinal Integrated Clerkships, suggesting they manifest their benefits and influence identity through continuity, relationships and responsibility.